2007
DOI: 10.1158/0008-5472.can-06-2759
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ–Independent Suppression of Androgen Receptor Expression by Troglitazone Mechanism and Pharmacologic Exploitation

Abstract: Previously, we showed that the peroxisome proliferatoractivated receptor ; (PPAR;) agonist troglitazone at high doses was able to suppress androgen receptor (AR) expression in LNCaP prostate cancer cells independently of PPAR;. Pharmacologic exploitation of this finding led to STG28, a PPAR;-inactive analogue of troglitazone with substantially higher potency in AR repression. Considering the pivotal role of AR in prostate tumorigenesis, this study investigates the mechanism by which troglitazone and derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 45 publications
4
62
2
Order By: Relevance
“…The results indicate that ␤-CDODA-Me inhibits AR transcription without the parallel induction of inhibitory transacting factors. Recent studies suggest that AR down-regulation of a PPAR␥-inactive thiazolidinedione analog was due to down-regulation of Sp1 protein (Yang et al, 2007). Results in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…The results indicate that ␤-CDODA-Me inhibits AR transcription without the parallel induction of inhibitory transacting factors. Recent studies suggest that AR down-regulation of a PPAR␥-inactive thiazolidinedione analog was due to down-regulation of Sp1 protein (Yang et al, 2007). Results in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…To understand whether PPAR␣ or PPAR␥ is involved in the inhibitory effect of DHA on SOD-1 gene expression, cells were treated with 20 M troglitazone, a PPAR␥ agonist (Adams et al, 1997), and 500 M clofibrate, a PPAR␣ agonist (Göttlicher et al, 1992), for 20 h. The concentrations of troglitazone and clofibrate were chosen based on previous studies (Canuto et al, 2003;Hashimoto et al, 2004;Yang et al, 2007). Luciferase activity assay indicated that clofibrate suppresses SOD-1 gene transcription, whereas troglitazone does not (Fig.…”
Section: Ppar␣ Ligand Mimics the Effects Of Dha On Sod-1 Gene Transcrmentioning
confidence: 99%
“…Multiple preclinical studies show anti-cancer effects of thiazolidinediones (TZDs) PPARÁ agonist ligands (2)(3)(4)(5)(6). In contrast, clinical studies suggest that TZDs are largely ineffective as monotherapeutic agents in treating PCa (7).…”
Section: Introductionmentioning
confidence: 99%